Interação entre surfatantes na flotação de minérios de ferro - Ronney Rogerio Rodrigues Silva (2008)
There is considerable room for the development of joint application of frothers and amine on iron ore reverse cationic flotation. The use of the frothers in this application is few explored, because in pH usually applicable the collector does the function of collector and frother. Recent studies have shown that an interaction between the collector and the frothers exists. Such an interaction can be good or synergic for the flotation or it can be hinder flotation performance, depending upon the frother utilized. Studies performed with intention of best evaluating the variables that affect this interaction were performed at laboratory, pilot and industrial scales. The reagents used were several types of collector, where the main one was a cationic collector of the class of acetate of alkyl amines and several types of frothers that were added in severalproportions to the collector. With relation of the type of frother, it can be concluded that the best reagents of this class were C8 (alcohol), M9837 (alcoholC4-18, aldehydes, esters) and 01 DU133 (information not available) that had presented high metallic recoveries with goodselectivity, with the prominence biggest for the M9837 that presented the biggest recoveries. The frothers C8C10 (alcohol), 029/05 BD (based on alky phenol etoxylate) and M537 (information not available) had shown the best selectivity, however the frothers C8C10 (alcohol) and BD 029/05 (based on alky phenol etoxylate) obtained the best overall results. The compatibility between the structures of the surfactants (collector and frother) showed, one more time, its importance for good flotation performance. Best surfactants were represented by those that have compatible molecular structure with the tested amine The type of collector also seems to influence significantly in the final performance; thestructure and the degree of neutralization seem to have an important influence in the interaction of amine with frother. The tests with diamine clearly had shown a significant interaction with MONTANOL 800. With regard to pH, the best performance took place at higher values, that is, between pH the 10.5 and 11.0. It is also important to state that the results of the tests with frother at pH 8 were better when compared with tests without frother at this same pH, notwithstanding with worse results in comparison with the tests at pH10.5. With regard to the solution concentration and the solution preparation, it was verified that diluted concentrations presented the best results. The solutions of frother andcollectors prepared jointly outperformed all other tests. Regarding to variation temperature of surfactant solution preparation it was verified thatat higher temperatures, the tests presented higher recoveries and at lower temperatures, they are more selective. The industrial application at VGR processing plant reveals the fully feasibility and the ease of application of the conditions tested herein